TWO-DIMENSIONAL DYNAMICS OF SPHERICAL GRAIN FLOATING ON THE PROPAGATING WAVE FLUID SURFACE - Sparisoma Viridi; Nurhayati Nurhayati; Johri Sabaryati; Dewi Muliyati (Spektra: Jurnal Fisika dan Aplikasinya, 2018)
Abstract Simulation of a spherical grain floating in fluid surface propagating sinusoidal wave is performed using molecular dynamics method by assuming that superposition of buoyant, gravitational, and viscous forces will make the grain to move in two-dimension. It is different than previous result, where the grain can only move in one-dimension since size of the grain Db << Î»f. In this work Db < Î»f so that direction of buoyant force must be considered. It is predicted theoretically that the two-dimensional motion tends to be a one-dimensional motion when Db/Î» less than a certain value, but it remains as a two-dimensional motion when more than that value. In 20 s of observation frequency of the sinusoidal wave can determine whether the grain will move in the same direction of the travelling wave or not. Keywords: grains, simulation, buoyant force, gravitational force, viscous force.